La apariencia del buen derecho en la suspensión del acto reclamado en el amparo indirecto: de la jurisprudencia a la ley - Muñoz Alvarado, Froylán (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
In the following report of this research, different concepts are being analyzed about the topic and over the theory, the legislation and the jurisprudence, taking care all over, that the affirmations or refusals, be properly establish; and particularly, in relation to the figure of the “appearance by right”, which since march 14th, 1996. Acquire compulsoriness in relation with the authorities that known the guarantee trial, and to be considered to solve about the adjournment of the claiming act, besides the others elements that establish the article 124 of the Protection Law; with this purpose was ratify by the JOINT SESSION OF THE SUPREME COURT OF JUSTICE OF THE NATION, solving the contradiction of the thesis 3/95, stir up in the sustained judgment by the Collegiate Session the Third in administrative matters of the First circuit and the Second by the Sixth circuit; however, until this date it has not been a sustained judgment to this jurisprudence to not be modify or uninterrupted; otherwise, the best it can happen, under jurisprudence, for the good of the caution measure as the own protection law. Is to reform the contradiction, as the fraction X of the article 107, of the Political Constitution of the United States of Mexico, and to the addition of the fumus boni iuris, as a substantial requirement to the concession of the adjournment measure, and based on this appearance (prejudice), the judge of guarantee can realize the unconstitutional or not of the claiming acts and base on it, adjournment or not of the acts of authority under caution.

El trabajo de investigación que se presenta, tiene como objetivo la obtención del grado de Maestro en Derecho en la División de Estudios de Posgrado de la Facultad de Derecho y Ciencias Sociales de la Universidad Michoacana de San Nicolás de Hidalgo; en éste, se desarrolla la tesis de: “La Apariencia del Buen Derecho en la Suspensión del Acto Reclamado en el Amparo Indirecto: de la Jurisprudencia a la Ley”, a través de ocho capítulos, los cuales reúnen los conceptos más importantes del tema tratado, como son: La evolución, antecedentes, naturaleza y modalidades de la suspensión del acto reclamado, en el amparo directo e indirecto; la teoría de los actos de autoridad para efectos del juicio de garantías; las formas de hacer efectiva la medida cautelar; los recursos que prevé la ley ante su concesión o negativa; el fumus boni iuris y el periculum in mora, como elementos de las medidas cautelares aplicados a la suspensión del acto reclamado; los argumentos para la propuesta de reforma y la figura de la apariencia del buen derecho en otros países; ello, con la finalidad de arribar a las correspondientes conclusiones y propuesta.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2007-0002; Suspensión; Acto reclamado; Amparo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/431